2011
DOI: 10.1007/s10661-011-2025-7
|View full text |Cite
|
Sign up to set email alerts
|

Trace element concentrations in surface estuarine and marine sediments along the Mississippi Gulf Coast following Hurricane Katrina

Abstract: Hurricanes are relatively frequent ecological disturbances that may cause potentially long-term impacts to the coastal environment. Hurricane Katrina hit the Mississippi Gulf Coast in August 2005, and caused a storm surge with the potential to change the trace element content of coastal surface sediments. In this study, surface estuarine and marine sediments were collected monthly following the storm from ten sites along the Mississippi Gulf Coast (Mobile Bay, Grand Bay Bayous Heron and Cumbest, Pascagoula, Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
2
1
Order By: Relevance
“…Nevertheless, there are few studies on temporal TM variability in polluted bottom sediments caused by the action of hydrodynamic processes. Some of them found no significant differences during the year related to rainfall events (Tan et al, 2016) or hurricanes (Warren et al, 2012), but pollution levels in these studies were lower than in our study area, so variability could be more difficult to detect. Other studies observed higher TM concentrations during the wet seasons than during the dry season (Najamuddin et al, 2016), or that sediment resuspension caused significant enrichments in TM in the water column (Bancon-Montigny et al, 2019), in agreement with our observations.…”
Section: Effects Of Storms On Sediments and Tm Contentcontrasting
confidence: 77%
“…Nevertheless, there are few studies on temporal TM variability in polluted bottom sediments caused by the action of hydrodynamic processes. Some of them found no significant differences during the year related to rainfall events (Tan et al, 2016) or hurricanes (Warren et al, 2012), but pollution levels in these studies were lower than in our study area, so variability could be more difficult to detect. Other studies observed higher TM concentrations during the wet seasons than during the dry season (Najamuddin et al, 2016), or that sediment resuspension caused significant enrichments in TM in the water column (Bancon-Montigny et al, 2019), in agreement with our observations.…”
Section: Effects Of Storms On Sediments and Tm Contentcontrasting
confidence: 77%
“…A study monitoring unlined coal ash ponds in Southeastern United States has found coal ash residuals in nearby water sources even in absence of any major flooding events ( 48 ). However, studies following Hurricane Katrina ( 49 , 50 ) found insignificant spatial and temporal changes for both PAH and trace metal concentrations in sediments from the Mississippi Gulf Coast over a year-long study period. In our study, evidence of metal and PAH contaminant re-distribution associated with Hurricane Florence flooding was found at the location that was closest to a documented coal ash spill ( 35 ).…”
Section: Discussionmentioning
confidence: 96%
“…The crab species present in the Mediterranean basin have a diverse diet which permits the absorption of different chemical elements, at various concentrations, depending on the food source. Availability of trace elements in sediments is dependent and controlled by metal interaction with pH variation, cationic exchange capacity, nutrient status, carbonates and organic matter contents, redox potential and sediments texture, as well as the contamination nature in terms of origin and characteristics of deposition and composition (Rubio et al, 2000(Rubio et al, , 2010Liu et al, 2011;Warren et al, 2012;Kalantzi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%